Time in target range for systolic blood pressure and stroke in people with and without diabetes: the Kailuan prospective cohort study - Yang, Yuxin; Wu, Shouling; Zhang, Jingdi; Liu, Yang; Yin, Mingjie; Huo, Zhenyu; Chen, Shuohua; Wang, Guodong; Xiao, Yao; Wang, Yue; Li, Yuanyuan; Deng, Jiawen; et al. (Frontiers in Endocrinology, 2025)
ObjectiveSystolic blood pressure time in target range (SBP-TTR) is an independent risk factor for stroke. We aimed to investigate the associations of SBP-TTR with stroke among participants with or without diabetes using data from the Kailuan study.MethodsWe included 28,591 participants [mean age, 57.5 years; 83.8% men; 23.2% with diabetes] from the Kailuan Study. Cox proportional hazards regression models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (95% CIs) of SBP-TTR on stroke in individuals with and without diabetes.ResultsAfter a median of 8.7 years follow-up, 2,206 stroke cases occurred. Among participants with diabetes, those with SBP-TTR 75%–100% (HR [95%CI]: 0.64 [0.49, 0.84]) had a lower risk of stroke compared to those with SBP-TTR 0%–25%. Among participants without diabetes, those with SBP-TTR 50%–75% (HR 0.75, 95% CI 0.64–0.88) and 75%–100% (HR [95%CI]: 0.62 [0.52, 0.73]) had a significantly lower risk of stroke. A significant interaction between diabetes status and SBP-TTR was observed (P for interaction = 0.03). Additionally, the restricted cubic spline analysis showed a non-linear relationship between SBP-TTR and stroke risk among participants with diabetes (P for non-linearity = 0.001), and a linear relationship among those without diabetes (P for non-linearity = 0.035).ConclusionHigher SBP-TTR was associated with a reduced risk of stroke among participants with or without diabetes. The findings underscore the importance of maintaining blood pressure within the target range to mitigate stroke risk, particularly emphasizing the need for stringent blood pressure control in diabetic patients.